2022
DOI: 10.1126/sciadv.abj5881
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in a semiconducting all-inorganic halide perovskite

Abstract: Ferroelectric semiconductors are rare materials with both spontaneous polarizations and visible light absorptions that are promising for designing functional photoferroelectrics, such as optical switches and ferroelectric photovoltaics. The emerging halide perovskites with remarkable semiconducting properties also have the potential of being ferroelectric, yet the evidence of robust ferroelectricity in the typical three-dimensional hybrid halide perovskites has been elusive. Here, we report on the investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 52 publications
2
62
0
Order By: Relevance
“…However, for FA, only one C−N bond of it is aligned along the c ‐axis and the other triple‐disordered C−N bond exhibits a C 3 v symmetry around the c ‐axis (Figure S8a). The distortion of the [GeBr 6 ] octahedra increases with the increasing organic cation size (Figure 2 and Table 1), which is accompanied by the change of bond length and angle, as well as the displacement of Ge 2+ along the [111] direction in the unit cell (Tables S6–S9 and Figure S6) [51, 55] . Noted that there are two kinds of Ge−Br bonds (short and long bond) due to the prominent lone pair effect of Ge 2+ .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, for FA, only one C−N bond of it is aligned along the c ‐axis and the other triple‐disordered C−N bond exhibits a C 3 v symmetry around the c ‐axis (Figure S8a). The distortion of the [GeBr 6 ] octahedra increases with the increasing organic cation size (Figure 2 and Table 1), which is accompanied by the change of bond length and angle, as well as the displacement of Ge 2+ along the [111] direction in the unit cell (Tables S6–S9 and Figure S6) [51, 55] . Noted that there are two kinds of Ge−Br bonds (short and long bond) due to the prominent lone pair effect of Ge 2+ .…”
Section: Resultsmentioning
confidence: 98%
“…and the interplay between ionic radius and the tolerance factor. [46][47][48][49][50][51] Chen et al reported a series of hybrid metal halide (C 6 H 5 (CH 2 ) 4 NH 3 ) 4 MX 7 •H 2 O (M = Bi, In, X = Br or I) with SHG responses. [46] Previously, we have reported a series of Ge-based iodide perovskites with excellent SHG properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and the interplay between ionic radius and the tolerance factor. [46][47][48][49][50][51] Chen et al reported a series of hybrid metal halide (C 6 H 5 (CH 2 ) 4 NH 3 ) 4 MX 7 •H 2 O (M = Bi, In, X = Br or I) with SHG responses. [46] Previously, we have reported a series of Ge-based iodide perovskites with excellent SHG properties.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly important structure–property relationship discovered in recent studies is related to the stereochemical expression of the 6s 2 lone pair on the Pb 2+ cation, , which causes dynamic or static distortion of the local octahedral geometry, as the resulting lone pair occupies one of the coordination sites. The dynamic lone-pair expression is likely responsible for the strong lattice anharmonicities and local polar fluctuations in LHPs, , whereas the static manifestation may give rise to inversion symmetry breaking and noncentrosymmetric structuresa prerequisite to properties such as ferroelectricity, even-order nonlinear optical properties, and Rashba–Dresselhaus effect. ,, …”
Section: Introductionmentioning
confidence: 99%